GK dimension of finite extensions

Posted: April 26, 2011 in Gelfand-Kirillov Dimension, Noncommutative Ring Theory Notes
Tags: , ,

The goal is to prove the following fundamental result: if an algebra A is a finite module over some subalgebra B, then {\rm{GKdim}}(A)={\rm{GKdim}}(B).

Lemma. Let B be a subalgebra of a k-algebra A. Suppose that, as a (left) module, A is finitely generated over B. Then  {\rm{GKdim}}({\rm{End}}_B(A)) \leq {\rm{GKdim}}(B).

Proof. So A=\sum_{i=1}^n Ba_i for some a_i \in A. Define \varphi: B^n \longrightarrow A by \varphi(b_1, \ldots , b_n)=\sum_{i=1}^n b_ia_i and let I = \ker \varphi. Let

C=\{f \in {\rm{End}}_B(B^n): \ f(I) \subseteq I \}.

Clearly C is a subalgebra of {\rm{End}}_B(B^n) \cong M_n(B). Now, given f \in C define \overline{f}: A \longrightarrow A by  \overline{f}(a)=\varphi f (u), where u is any element of B^n with \varphi(u)=a. Note that \overline{f} is well-defined because if \varphi(v)=a for some other v \in B^n, then u-v \in I and so f(u-v) \in I. Hence 0=\varphi f(u-v)=\varphi f(u) - \varphi f(v) and so \varphi f(u) = \varphi f(v). It is easy to see that \overline{f} \in {\rm{End}}_B(A)). Finally, define \psi: C \longrightarrow {\rm{End}}_B(A)) by \psi(f)=\overline{f}. Then \psi is an k-algebra onto homomorphism and hence

{\rm{GKdim}}({\rm{End}}_B(A)) \leq {\rm{GKdim}}(C) \leq {\rm{GKdim}}(M_n(B)) ={\rm{GKdim}}(B),

by Fact 1 and Fact 5. \Box

Theorem. Let B be a subalgebra of a k-algebra A and suppose that, as a (left) module, A is finitely generated over B. Then {\rm{GKdim}}(A)={\rm{GKdim}}(B).

Proof. The algebra A has a natural embedding into {\rm{End}}_B(A) and so {\rm{GKdim}}(A) \leq {\rm{GKdim}}({\rm{End}}_B(A)). Thus {\rm{GKdim}}(A) \leq {\rm{GKdim}}(B), by the lemma. \Box

An important consequence of the above theorem is the following result. It shows that for finitely generated commutative algebras, GK dimension is nothing but the transcendence degree of the algebra over the base field.

Corollary. If A is a finitely generated commutative k-algebra, then {\rm{GKdim}}(A)={\rm{tr.deg}}(A/k).

Proof. Let m={\rm{tr.deg}}(A/k). Then A contains a polynomial k-algebra B=k[x_1, \ldots, x_m] such that A is a finitely generated B-module, by the  Noether normalization theorem. Thus, by Corollary 2 and this theorem, {\rm{GKdim}}(A) = {\rm{GKdim}}(B)=m. \Box

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s